Associations between women's perceptions of gender relations and self-esteem and self-efficacy in a former conflict zone: baseline findings in South Kivu, DR Congo - Clea Sarnquist; Rasika Behl; Aisha Talib; Jonathan Altamirano; Barbara Jerome; Joseph Inungu; Yvonne Maldonado (Elsevier, 2018)
Background: Eastern DR Congo is recovering from decades of armed conflict in which violence against women (VAW) was widely used as a weapon of war. Even now, rates remain high: 34·5% and 47·5% of women in South Kivu report ever experiencing sexual or physical violence, respectively. However, there are few data on the impact of VAW on the health of women and their children. Methods: In August 2016, we collected baseline data on demographic and health-related variables from mothers of children younger than 5 years in 843 households enrolled as part of a larger impact evaluation. Women's empowerment was measured using the previously validated Rosenberg's self-esteem scale (RSES), the generalised self-efficacy scale (GSES), and a gender relations scale originally developed by the Medical Research Council of South Africa. GSES and RSES scores were generated by averaging individual responses to questions; bivariate analyses of the scores with individual gender relations questions were conducted using χ2 tests. Findings: Of the 845 mothers interviewed, 325 (45·5%) had less than a primary education. The mean number of children younger than 18 years per household was four, with 66 (8%) of households having more than seven such children. Mean self-esteem score was 18·2 (SD 5·3) and mean self-efficacy score was 26·2 (SD 6·3), and internal reliability tests of the RSES and GSES scales yielded alphas of α=0·76 and α=0·89, respectively. Women with higher GSES or RSES scores were less likely to accept physical violence or sexual coercion than women with lower scores (p<0·05); however, perception of male authority and gender roles within the household did not vary by score. Interpretation: This population of women had lower self-esteem than for a generalised population in DR Congo (21·3), probably because of the prolonged conflict in eastern DR Congo. Furthermore, mean GSES was lower than that of another post-conflict setting (Iran, 30·2), as well as several higher-income countries (29-32). Funding: American Refugee Committee.